PENGARUH PROMOSI JABATAN, TINGKAT ABSENSI DAN DISIPLIN TERHADAP KINERJA PEGAWAI PADA DINAS PEMUDA, OLAHRAGA, KEBUDAYAAN DAN PARIWISATA KOTA TANJUNG BALAI - Dailami Dailami (Jurnal Akrab Juara, 2018)
This research is an indication that the employee's performance is not maximal in Tanjung Balai City's Youth, Sports, Culture and Tourism Office. There are still many obstacles in carrying out tasks and employees cannot work optimally. The method used in this study is a survey approach. This type of quantitative descriptive research and the nature of research are explanations. Data collection method is by interview, questionnaire and documentation study. The population is all employees in the Department of Youth, Sports, Culture and Tourism of the Tanjung Balai City, namely 38 employees and the number of employees from the entire population is 38 employees. The results showed that simultaneously there was a significant influence between job promotion, absenteeism and discipline on the performance of employees at the Office of Youth, Sports, Culture and Tourism of Tanjung Balai City and partially showed a significant influence between job promotion, absenteeism and discipline the performance of employees at the Tanjung Balai City Youth, Sports, Culture and Tourism Office and partially the most dominant influence on employee performance is discipline.